2002
DOI: 10.1159/000064583
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Mucinous Gastric Carcinoma

Abstract: Background/Aims: Mucinous gastric carcinoma (MGC) is a histopathologic subtype of gastric carcinoma with a poor prognosis. The purpose of this study was to compare the disease course of MGC with non-mucinous gastric carcinoma (NMGC) and study the clinicopathologic features that influence the prognosis of MGC patients. Methods: We reviewed the records of 2,383 patients with a confirmed histologic diagnosis of gastric carcinoma. There were 157 patients with MGC compared to 2,226 with NMGC. Results: A depth of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 5 publications
1
20
3
Order By: Relevance
“…Kawamura et al 1 reported that MGC was frequently observed in younger patients and that most MGC were located in the lower third of the stomach. However, the results of the present study, and studies by other investigators, 2,3,12 have shown no significant differences between MGC and NGC in age and tumour location.…”
Section: Mucinous Gastric Carcinomacontrasting
confidence: 76%
See 1 more Smart Citation
“…Kawamura et al 1 reported that MGC was frequently observed in younger patients and that most MGC were located in the lower third of the stomach. However, the results of the present study, and studies by other investigators, 2,3,12 have shown no significant differences between MGC and NGC in age and tumour location.…”
Section: Mucinous Gastric Carcinomacontrasting
confidence: 76%
“…3,12 Kawamura et al 1 also reported that MGC patients had a higher frequency of peritoneal metastasis than NGC patients, whereas the results of Woo et al 2 showed no significant difference between MGC and NGC, in this measure. Peritoneal metastasis was not included in the present investigation because of the small sample size.…”
Section: Mucinous Gastric Carcinomamentioning
confidence: 95%
“…Thus, previous reports on SRC or MC have involved comparative analyses of SRC and MC versus non-SRC or non-MC [1,2,[13][14][15][16][17]. However, SRC and MC tumors have much in common as they are both undifferentiated and mucin-producing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although these histologic subtypes have been well studied, it is still debatable as to how their histologic types are related to clinicopathologic findings and outcome [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In our patient, the tumor had massive peritoneal dissemination, and its histological type was mainly mucinous gastric carcinoma. In general, this histological type has been reported to be more advanced in stage at the time of diagnosis, with a higher rate of peritoneal dissemination than nonmucinous gastric carcinomas [16][17][18]. Some reports indicate no difference in prognosis between patients with mucinous and nonmucinous gastric cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%